Impact of quarantine on stress management, inter-personal, and spiritual growth of quarantined nurses - Montilijao, Richard S.; Arnibal , Sheila P. (Technium Social Sciences Journal, 2024)
Due to the outbreak of coronavirus disease, 83% of households experienced a reduction in income, more than 25% of Filipinos reported anxieties, and 66,000 deaths from coronavirus disease 2019 (COVID-19) have been reported. With the pandemic, nurses are an essential part of the healthcare industry. With the notion that nurses now handle a variety of patients, sometimes nurses neglect their health. This study bridges the gap between the nurses’ health situation when afflicted with COVID-19, and how they can manage their health in terms of stress management, interpersonal, and spiritual aspects while in quarantine. Thus, using the quantitative design, this study determined the extent of impact of quarantine on the stress management, interpersonal, and spiritual growth of nurses who were infected with COVID-19 and experienced quarantine in Negros Occidental when they were taken as a whole and grouped according to age, sex, civil status, areas of the hospital, and types of quarantine facility. Also, it investigated on the relationship between the demographics and the impact of quarantine on stress management and interpersonal and spiritual growth of nurses. The study determined a very great extent of quarantine impact on the stress management, interpersonal, and spiritual growth of nurses who were infected with COVID-19 and experienced quarantine in Negros Occidental. There was a significant relationship for age and areas of the hospital on the impact of quarantine; while there was no significant relationship for the variables sex, civil status, and types of quarantine facilities on the impact of quarantine. It is essential to recognize that stress is a subjective experience that varies from person to person; it is crucial for policymakers and healthcare providers to recognize the importance of addressing the mental health needs of individuals in quarantine facilities. At the same time, the administrators should recognize and address different challenges encountered by nurses in quarantine to ensure their well-being.